Yunis-Varón syndrome caused by biallelic VAC14 mutations - Lines, Matthew A (Eur J Hum Genet, 2017)
Yunis-Varón syndrome (YVS) is an autosomal recessive disorder comprising skeletal anomalies, dysmorphism, global developmental delay and intracytoplasmic vacuolation in brain and other tissues. All hitherto-reported pathogenic variants affect FIG4, a lipid phosphatase involved in phosphatidylinositol (3,5)-bisphosphate [PtdIns(3,5)P(2)] metabolism. FIG4 interacts with PIKfyve, a lipid kinase, via the adapter protein VAC14; all subunits of the resulting complex are essential for PtdIns(3,5)P(2) synthesis in the endolysosomal membrane compartment. Here, we present the case of a female neonate with clinical features of YVS and normal FIG4 sequencing; exome sequencing identified biallelic rare coding variants in VAC14. Cultured patient fibroblasts exhibited a YVS-like vacuolation phenotype ameliorated in a dose-dependent fashion by ML-SA1, a pharmacological activator of the lysosomal PtdIns(3,5)P(2) effector TRPML1. The patient developed a diffuse leukoencephalopathy with loss of the normal N-acetylaspartate spectrographic peak and presence of a large abnormal peak consistent with myoinositol. We report that VAC14 is a second gene for Yunis-Varón syndrome.